Development of a model for virtual leadership behavior on knowledge sharing in online programming communities - Al-Mashhadani, Abdulrazak F. Shahatha (2019)
Despite the significant increase in the number of emerging online programming communities, very few succeed in inspiring members to share their knowledge. Recent studies have focused on personal level factors in encouraging members’ knowledge sharing. However, limited studies emphasis on the role of leader. In addressing this gap, this study aims to develop a model to examine the role of virtual leadership towards knowledge sharing in online programming communities. Then in carrying out the objective, the examination of virtual leadership behaviour moderating members’ personal cognitive factors toward knowledge sharing was conducted. Social Cognitive Theory and Path Goal Theory are used as the basis for the proposed model. The proposed model is tested empirically using data collected from 20 online programming communities. The result suggests that different leadership behaviors significantly moderate the effect of self-efficacy and outcome expectancy on members’ knowledge sharing. This finding implies that although online communities are informal in nature, the appropriate type of leadership can boost members’ efficacy and outcome expectancy to participate in knowledge sharing. Ideally, with the appropriate level of autonomy and recognition of members contributions can motivate members to continuously contribute to online programming communities and promote the sustainability of this platform. The implication of this study will provide meaningful insights for system designers to include several features to facilitate leadership behaviors in online programming communities. In supporting participative-leadership behavior, online poll and online voting need to be accommodated to allow inclusive decisions by members. Additionally, ranking and reputation features can further facilitate the achievement-oriented leadership and increase knowledge sharing among online programming community members.